Hyperacusis: An Overview - Baguley, David M. (Seminars in Hearing, 2014)
Hyperacusis (decreased sound tolerance) can be extremely troublesome for affected individuals and their families. Many terms are used to describe sound tolerance symptoms in the clinical literature, and this has led to some confusion. There are associations between hyperacusis and otologic, developmental, neurological, and psychological disorders, and these are described. Work is underway regarding physiological mechanisms, with an increase in central auditory gain an area of interest, but this work is emergent at present. There is a clinical association between hyperacusis and tinnitus, with 40% of persons with troublesome tinnitus also experiencing decreased sound tolerance, but causality is not yet understood. The evaluation of a patient with hyperacusis involves a careful history and a cautious approach to audiological investigation, particularly regarding assessment of loudness tolerance. Questionnaire instruments exist for the assessment of hyperacusis, but none are designed for use with children. Many unanswered questions about decreased sound tolerance exist, and some of these are described.
Keywords: Hyperacusis; decreased sound tolerance; tinnitus; auditory gain